Analysis of Sports Injury History of Cricket Athletes at the 9th East Java Province Championship - Muhammad Diffa Ali Dzikri; Yulingga Nanda Hanief (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2025)
This study aims to analyze the types of injuries, injury locations, and initial treatment of sports injuries experienced by cricket athletes at the 9th East Java Provincial Sports Week (PORPROV). In Indonesia, research on cricket injuries remains limited, particularly in multi-event competitions such as the East Java Provincial Sports Week (PORPROV). This study employed a quantitative descriptive approach with a cross-sectional design and a purposive sampling technique. The population consisted of 280 cricket athletes who participated in the 9th PORPROV, and data were collected using a validated questionnaire. The inclusion criteria included athletes who experienced injuries during the competition and were willing to participate in the study. The data were analyzed using percentage techniques to describe the distribution of injuries. A total of 37 injury cases were recorded. The most common types of injuries were bruising (37.8%), followed by muscle cramps (21.6%), and sprains and strains (13.5% each). The most frequently injured body parts were the thighs/hamstrings (27.0%), followed by the feet (18.9%) and fingers (13.5%). In terms of initial treatment, the RICE method (45.94%) was the most commonly used, followed by the use of pain relief sprays (40.54%). Injury prevention programs can be made more effective by optimizing warm-ups, strengthening relevant muscle groups, and improving the readiness of facilities and medical support staff at the match venue.